Beliefs in vaccine as causes of autism among SPARK cohort caregivers. Issue 7 (11th February 2020) - ,; Abbeduto, Leonard; Aberbach, Gabriella; Acampado, John; Ace, Andrea J.; Albright, Charles; Alessandri, Michael; Amaral, David G.; Amatya, Alpha; Anglo, Claudine; Annett, Robert D.; Arriaga, Ivette; et al.
Abstract: Background: Fear of autism has led to a decline in childhood-immunization uptake and to a resurgence of preventable infectious diseases. Identifying characteristics of parents who believe in a causal role of vaccines for autism spectrum disorder (ASD) in their child may help targeting educational activities and improve adherence to the immunization schedule. Objectives: To compare caregivers of children with ASD who agree or disagree that vaccines play an etiological role in autism for 1) socio-demographics characteristics and 2) developmental and clinical profiles of their children. Methods: Data from 16, 525 participants with ASD under age 18 were obtained from SPARK, a national research cohort started in 2016. Caregivers completed questionnaires at registration that included questions on beliefs about the etiologic role of childhood immunizations and other factors in ASD. Data were available about family socio-demographic characteristics, first symptoms of autism, developmental regression, co-occurring psychiatric disorders, seizures, and current levels of functioning. Results: Participants with ASD were 80.4% male with a mean age of 8.1 years (SD = 4.1). Overall, 16.5% of caregivers endorsed immunizations as perceived causes of autism. Compared to caregivers who disagreed with vaccines as a cause for ASD, those who believed in vaccine causation came disproportionately from ethnic minority, less educated, and less wealthy backgrounds. More often their children had experienced developmental regression involving language and other skills, were diagnosed earlier, had lost skills during the second year of life, and had worse language, adaptive, and cognitive outcomes. Conclusion: One in six caregivers who participate in a national research cohort believe that child immunizations could be a cause of autism in their child. Parent social background (non-White, less educated) and child developmental features (regression in second year, poorer language skills, and worse adaptive outcomes) index caregivers who are more likely to harbor these beliefs and could benefit from targeted educational activities.